2013
DOI: 10.7150/ijbs.6996
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 Regulates Endothelial Permeability by Down-regulation of Tight Junction but not Dependent on Integrins Induced Focal Adhesions

Abstract: Interleukin-8 (IL-8) is a common inflammatory factor, which involves in various non-specific pathological processes of inflammation. It has been found that increased endothelial permeability accompanied with high expression of IL-8 at site of injured endothelium and atherosclerotic plaque at early stages, suggesting that IL-8 participated in regulating endothelial permeability in the developing processes of vascular disease. The purpose of this study is to investigate the regulation effects of IL-8 on the vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 50 publications
6
76
0
2
Order By: Relevance
“…In Caco-2 cells, studies showed that TNFa down-regulated the expression of ZO-1 [76] and Occludin [77] respectively. Moreover, IL-8 decreased the mRNA level of Occludin, Claudin-5 and ZO-1 in human [78]. In the present study, valine deficiency increased the IL-8 and TNF-a expression in the fish intestine, indicating that valine deficiency down-regulated the expression of Occludin and ZO-1 may be attributed to the upregulation of TNF-a and IL-8 in the intestine for fish.…”
Section: Valine Regulated Tj Protein Transcript Abundance In the Intesupporting
confidence: 55%
“…In Caco-2 cells, studies showed that TNFa down-regulated the expression of ZO-1 [76] and Occludin [77] respectively. Moreover, IL-8 decreased the mRNA level of Occludin, Claudin-5 and ZO-1 in human [78]. In the present study, valine deficiency increased the IL-8 and TNF-a expression in the fish intestine, indicating that valine deficiency down-regulated the expression of Occludin and ZO-1 may be attributed to the upregulation of TNF-a and IL-8 in the intestine for fish.…”
Section: Valine Regulated Tj Protein Transcript Abundance In the Intesupporting
confidence: 55%
“…TNF-a and IL-1b down-regulate the expression of ZO-1 [59] and Occludin [60], respectively, in Caco-2 cells. Moreover, IL-8 decreased Occludin, Claudin-5 and ZO-1 mRNA levels in human vascular endothelial cells [61]. IL-1b, IL-8 and TNF-a expression in the present study increased significantly in valine-limited diet group.…”
Section: Valine Regulating Tight Junction Protein Transcript Abundancsupporting
confidence: 55%
“…Vascular endothelium is a semipermeable membrane formed by vascular endothelial cell monolayer and localized at the critical interface between the blood and vessel wall [34], which could regulate the exchange balance of dissolved gases, ions and solutes between the inner and outer of vascular endothelium and supply the essential nutrients needed for the normal physiological functions of organs [56]. Vascular hyperpermeability means that it in part lost semipermeable characteristics, which is the hallmark of inflammatory diseases such as atherosclerosis [13] and involved in the development of heart and lung edema, shock and tumor angiogenesis [4].…”
Section: Discussionmentioning
confidence: 99%